2021
DOI: 10.3390/ijerph182111023
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of a Calamansi-Containing Energy Drink on Running Performance and Recovery in NCAA Division I Middle-Distance Runners: A Preliminary Study

Abstract: This study examined the effects of a non-caffeinated energy drink (ED) that contained calamansi juice, glucose, and taurine on 3-km running performance and recovery. Eleven NCAA Division I middle-distance runners (20.8 ± 1.5 years old) were randomly assigned to consume either the ED or a placebo drink 60 min before 3-km running on a 400-m official track. Performance time and speed were recorded every 500-m interval. Recovery blood lactate concentration (BLC), systolic (SBP), diastolic blood pressure (DBP), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Placebo: 358 ± 35 W). [ 141 ] Sünram-Lea et al 2012 81 firefighter trainees (26 ± 10 y, 80.6 ± 17.1 kg) Randomized, double-blind, placebo-controlled, crossover study ED containing 40 mg caffeine and 50 g carbohydrates vs. ED with 80 mg caffeine and 10.25 g carbohydrates vs. placebo 75 min prior to exercise testing Handgrip test ↑ Handgrip strength after consumption of ED containing 40 mg caffeine and 50 g carbohydrates [ 148 ] Eckerson et al 2013 17 physically active men (21 ± 1 y, 85.5 ± 9.3 kg) Randomized, double-blind, placebo-controlled, crossover study ED (Sugar-free Red Bull®) containing 160 mg caffeine and 2000 mg taurine vs. a caffeine only drink (160 mg) vs. a non-caloric placebo 60 min prior to exercise testing 1RM BP ↔ 1RM BP [ 151 ] Del Coso et al 2013a 16 elite female rugby players (23 ± 2 y, 66 ± 7 kg) Randomized, double-blind, placebo-controlled, crossover study ED (Fure®, ProEnergetics: 3 mg∙kg BW −1 caffeine, taurine 2000 mg, sodium bicarbonate 500 mg, L-carnitine 200 mg, and maltodextrin 705 mg) vs. placebo 60 min prior to exercise testing 15s maximal jump test ↑ Power output during jump test [ 169 ] Abien-Vicen et al 2014 16 young basketball players (14.9 ± 0.8 y, 73.4 ± 12.4 kg) Randomized, double-blind, placebo-controlled, crossover study ED (Fure®, ProEnergetics: 3 mg∙kg BW −1 caffeine, taurine 2000 mg, sodium bicarbonate 500 mg, L-carnitine 200 mg, and maltodextrin 705 mg) vs. placebo 60 min prior to exercise testing CMVJ test 15s maximal jump test ↑ CMVJ jump height (38.3 ± 4.4 vs. 37.5 ± 4.4 cm) ↑ Jump height in 15s jump test (30.2 ± 3.4 vs. 28.8 ± 3.4 cm). [ 134 ] Del Coso et al 2014 15 male volleyball players (21.8 ± 6.9 y, 66 ± 7 kg) Randomized, do...…”
Section: Acute Exercise Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Placebo: 358 ± 35 W). [ 141 ] Sünram-Lea et al 2012 81 firefighter trainees (26 ± 10 y, 80.6 ± 17.1 kg) Randomized, double-blind, placebo-controlled, crossover study ED containing 40 mg caffeine and 50 g carbohydrates vs. ED with 80 mg caffeine and 10.25 g carbohydrates vs. placebo 75 min prior to exercise testing Handgrip test ↑ Handgrip strength after consumption of ED containing 40 mg caffeine and 50 g carbohydrates [ 148 ] Eckerson et al 2013 17 physically active men (21 ± 1 y, 85.5 ± 9.3 kg) Randomized, double-blind, placebo-controlled, crossover study ED (Sugar-free Red Bull®) containing 160 mg caffeine and 2000 mg taurine vs. a caffeine only drink (160 mg) vs. a non-caloric placebo 60 min prior to exercise testing 1RM BP ↔ 1RM BP [ 151 ] Del Coso et al 2013a 16 elite female rugby players (23 ± 2 y, 66 ± 7 kg) Randomized, double-blind, placebo-controlled, crossover study ED (Fure®, ProEnergetics: 3 mg∙kg BW −1 caffeine, taurine 2000 mg, sodium bicarbonate 500 mg, L-carnitine 200 mg, and maltodextrin 705 mg) vs. placebo 60 min prior to exercise testing 15s maximal jump test ↑ Power output during jump test [ 169 ] Abien-Vicen et al 2014 16 young basketball players (14.9 ± 0.8 y, 73.4 ± 12.4 kg) Randomized, double-blind, placebo-controlled, crossover study ED (Fure®, ProEnergetics: 3 mg∙kg BW −1 caffeine, taurine 2000 mg, sodium bicarbonate 500 mg, L-carnitine 200 mg, and maltodextrin 705 mg) vs. placebo 60 min prior to exercise testing CMVJ test 15s maximal jump test ↑ CMVJ jump height (38.3 ± 4.4 vs. 37.5 ± 4.4 cm) ↑ Jump height in 15s jump test (30.2 ± 3.4 vs. 28.8 ± 3.4 cm). [ 134 ] Del Coso et al 2014 15 male volleyball players (21.8 ± 6.9 y, 66 ± 7 kg) Randomized, do...…”
Section: Acute Exercise Performancementioning
confidence: 99%
“…As mentioned above in the section on power production, the research group of Del Coso and colleagues performed a series of investigations examining the ergogenic potential of ED formulations providing 3 mg∙kg BW −1 caffeine on various aspects of sport performance. The researchers recruited a wide variety of athletes, finding that consumption of an ED resulted in a greater total distance covered at a speed greater than 13 km∙h −1 during a simulated soccer match in semiprofessional soccer players [ 135 ], greater running speed during a rugby sevens competition in elite female rugby athletes [ 137 ], increased total distance covered during a simulated competition in elite male rugby athletes [ 169 ] and college-aged female soccer athletes [ 138 ], as well as increased distance covered while running at high intensity during a simulated competition in male field hockey players [ 170 ]. Additionally, the researchers found that ED consumption resulted in a faster high intensity running pace during a tennis match in elite junior tennis players compared to placebo [ 147 ].…”
Section: Aerobic Exercisementioning
confidence: 99%
See 1 more Smart Citation